Increased Incidence of Functional Constipation in Children with a History of Perianal Abscess—A Single-Center Retrospective Cohort Study - Deffaa, Oliver Johannes; Gosemann, Jan Hendrik; Lacher, Martin; Wagner, Richard (European Journal of Pediatric Surgery, 2020)
Introduction Functional constipation (FC) is a common gastrointestinal disorder affecting up to 30 % of children. Voluntary stool withholding (e.g., after painful defecation) with consecutive harder and larger stools can result in avoidance patterns. Perianal abscesses (PA) are associated with anal pain and painful stooling. We hypothesized that patients with PA have a higher incidence of subsequent FC compared with children without PA.Materials and Methods Between January 2010 and December 2016, we retrospectively analyzed all infants (< 365 days of life) presenting at our institution with PA or unilateral inguinal hernia repair (IH; control group). We screened the clinical charts of these patients for outpatient or inpatient visits due to FC according to ROME IV criteria between 01/2010 and 10/2019. Statistical analysis was done using chi-squared test.Results We included a total of 37 infants with PA and 118 with IH repair (controls). Mean age at presentation for PA was 3.7 ± 0.5 months compared with 4.2 ± 0.3 months at surgery for IH. In the PA group, 6/37 (16%) developed FC compared with 1/118 (1%) in the control group (p-value < 0.01). Patients with PA presented with FC at a mean age of 22.3 ± 4.6 months. Twenty-three of thirty-seven (62%) of PA patients underwent surgery. The development of FC in the PA group was independent of conservative versus surgical treatment (14 vs. 17%, p >0.05).Conclusion Our study suggests that PA is associated with an increased risk of FC during the further course. Prophylactic stool softening in patients with PA may be considered to prevent subsequent FC.
Keywords: perianal abscess; functional constipation; children